178k views
3 votes
If f(x)=x-1/3 and g(x)=3x+1, what is (f*g)(x) 3x+1 x-3

If f(x)=x-1/3 and g(x)=3x+1, what is (f*g)(x) 3x+1 x-3-example-1
User SergeevDMS
by
5.2k points

2 Answers

1 vote
This is a composite. Another way to write them is f(g(x)). Take the function g(x) and stick it in for x in f(x). Like this:
f(g(x))= ((3x+1)-1)/(3). But we aren't done cuz there's some simplifying there to do.
f(g(x))= (3x)/(3) and canceling out the 3's we get just a simple x as our answer. The choice is the last one above as your answer.
1 vote
The correct answer is: [D]: " x " .
_________________________________________________________
Step-by-step explanation:
_________________________________________________________

f (g(x)) = f(3x + 1) = (3x + 1 - 1) / 3 = (3x / 3) = x .

The answer is: " x " .

→ which is: "Answer choice: [D]: " x " .
_________________________________________________________
User Jonah Benton
by
5.9k points